Meningkatkan Daya Tarik Pembelajaran Matematika di SMPS PTPN IV BAH JAMBI SIMALUNGUN Melalui Program Kampus Mengajar - Stepani Grace Zebua; Kondios Mei Darlin Pasaribu; Ellyawati Lubis (Participative Journal: Jurnal Pengabdian Pada Masyarakat, 2023)
The Teaching Campus Program is one of the Independent Learning Campus Merdeka (MBKM) programs in the form of teaching assistants to empower students in helping the learning process in junior high schools in various villages/cities, one of which is PTPN IV BAH JAMBI PRIVATE SMP, Simalungun Regency, Prov. North Sumatra. In this program, students are responsible for assisting the school in the teaching process, assisting technology adaptation, and assisting administration. In addition, students have a responsibility to improve students morals and increase students motivation and interest in learning during this pandemic. The results of this program are expected to grow social sensitivity in students to help the surrounding community, hone thinking skills in working together with both teachers and students across disciplines in solving problems they face, and develop students' insight, character, and Soft Skills, so that with collaboration above will the objectives that exist in the campus teaching program are achieved.